Corporate commitment to climate change: The effect of eco-innovation and climate governance - Albitar, Khaldoon; Al-Shaer, Habiba; Liu, Yang Stephanie (Research Policy, 2023)
Climate change represents a significant problem to the planet which raises concerns from stakeholder groups about corporate commitment to climate change issues. In this paper, we explore the effect of eco-innovation and climate governance on corporate commitment to climate change. We develop a unique measure for climate change commitment by considering four components, viz. whether a company supports the Sustainable Development Goal 13 on climate action, whether a company is aware that climate change can represent commercial risks or opportunities, whether a company reports Scope 3 CO2 emissions and whether a company sets a target for emission reduction. We measure eco-innovation by using a score collected from the Eikon database that reflects a company's capacity to reduce environmental costs, eco-innovation intensity measured as environmental expenditures over revenues. We also create an index computed as a composite score by totalling five eco-innovation proxies collected from the Eikon database that reflect companies' efforts to reduce environmental impact. Concerning climate governance, we focus on three proxies, namely the existence of an environmental committee, climate incentives and the existence of sustainability reports. Based on a sample of companies listed on the London Stock Exchange for the period of 2014–2020, we find that corporate eco-innovation is positively associated with climate change commitment. We argue that firms that adopt innovative approaches to efficiently control pollution and resource use and reduce their environmental impact are more committed to climate change. We also find that climate governance is positively associated with climate change commitment. We claim that companies that integrate climate change issues in governance can help address climate change risks and opportunities. Our empirical evidence provides recommendations for managers and policymakers to promote the adoption of eco-innovative technologies and integrate climate change issues in governance, which can contribute to corporate commitment to climate change.